The Use of the Trance Method in Exploring Students' Dance Talents - Virno Bolu, Waode Muriani Ekasari; Sari, Yussi Ambar; Mulisa, Mulisa; Djahali, Putri Ayu (Journal of English Language and Education, 2025)
This study investigates the use of the trance method as an innovative approach to exploring and developing the dance talents of 4th and 5th-grade students at SD 2 Baubau. The trance method involves guiding learners into a transformative state that enhances their creativity and expression. In this state, learners experience a deeper connection with their bodies and emotions, enabling them to explore dance movements and expressions authentically and personally. The method also aims to improve learners' focus and concentration, allowing them to quickly grasp dance movements, refine techniques, and enhance their skills more effectively. The research process includes six stages: (1) observing students in grades 4 and 5, (2) analyzing their dance talents, (3) classifying students based on their abilities, (4) implementing the trance method, (5) fostering movement creativity, and (6) documenting the findings. The results of this study are intended to serve as a reference for teachers in organizing extracurricular activities, providing practical strategies to unlock students’ creativity and nurture their dance talents. This research highlights the potential of the trance method as an effective tool for developing students’ interests and skills in dance, contributing to more engaging and personalized learning experiences.